PENGARUH BIAYA PRODUKSI DAN HARGA JUAL TERHADAP PENDAPATAN PETANI - achmad royhanah arrasyid (EKSYDA: Jurnal Studi Ekonomi Syariah, 2021)
Abstrak Revenue is an important factor in determining the profits and losses of a company. Profits and losses are obtained by comparing income with expenses or expenses incurred by income. One of the main economic indicators to measure the economic capacity of the community is the level of community income. The indicators discussed are only related to income and expenses. The results of the t-test analysis showed that the significance level of X1 was 0.041 (0.041 <0.05), and the t-count value was -1.129. The significance level of X2 is 0.002 (0.002 < 0.05) and the t value is 3.065. Based on the results of the study, it can be concluded that the effect of increasing the price of insecticide products on farmers' harvest significance. Farmers must pay attention to the production costs that must be incurred, and producers must prioritize a reasonable selling price in order to obtain a decent income for corn farmers. Keywords: Product prices, Farmers Sell and Harvest Abstrak Pendapatan merupakan faktor penting dalam menentukan keuntungan dan kerugian suatu perusahaan.Keuntungan dan kerugian diperoleh dengan membandingkan pendapatan dengan pengeluaran atau biaya yang dikeluarkan oleh pendapatan. Salah satu indikator ekonomi utama untuk mengukur kemampuan ekonomi masyarakat adalah tingkat pendapatan masyarakat. Indikator yang dibahas hanya terkait dengan pendapatan dan pengeluaran. Hasil analisis uji-t menunjukkan tingkat signifikansi X1 sebesar 0,041 (0,041<0,05), dan nilai thitung sebesar -1,129. Tingkat signifikansi X2 sebesar 0,002 (0,002 < 0,05) dan nilai t sebesar 3,065. Berdasarkan hasil penelitian dapat disimpulkan bahwa pengaruh kenaikan harga produk insektisida terhadap segnifikasi panen petani. Petani harus memperhatikan. Kata Kunci : harga Produk, Jual dan Panen Petani